2003
DOI: 10.1051/forest:2002072
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhization of Pinus halepensis Mill. and Pinus pinaster Aiton seedlings in two commercial nurseries

Abstract: -Two Mediterranean pine species (Pinus halepensis and Pinus pinaster) and seven fungi species (Pisolithus tinctorius, Lactarius deliciosus, L. sanguifluus, Suillus mediterranensis, S. collinitus, S. bellinii, and Rhizopogon roseolus) were selected for a mycorrhization study in two nurseries of SE Spain. Two types of inoculum (spore suspension and mycelium inoculum) were used on 3 700 pine seedlings. The aim of the study was to ascertain the influence of two different substrata (composted pine bark and fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
2
10
0
9
Order By: Relevance
“…The germination percentages obtained (except for CAL, which exhibited very low values) were similar to those recorded in other studies carried out in the Mediterranean Basin [5,12,18,20]. Differences in germination percentages for seeds collected from serotinous and nonserotinous cones have also been noted in other studies [15,24].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The germination percentages obtained (except for CAL, which exhibited very low values) were similar to those recorded in other studies carried out in the Mediterranean Basin [5,12,18,20]. Differences in germination percentages for seeds collected from serotinous and nonserotinous cones have also been noted in other studies [15,24].…”
Section: Discussionsupporting
confidence: 75%
“…This was due to the young age of these forests, since the higher number of trees with low individual cone production induce a large yield, although small numbers of trees with high individual cone production could produce similar yield. Similar situations have been identified in other studies [20,47]. In the case of open cones there was a positive correlation with site quality (climate), which favoured taller trees.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The minimal level of ECM necessary to ensure seedling performance in the field has been poorly studied, and probably depends on environmental characteristics of the site of transplantation and on the fungus-tree combination used [4,34]. The spore inoculum of P. tinctorius has been successfully used in previous experiments to produce containerised Pinus species, including P. pinea [15,28,32].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported a positive effect of P fertilization on maritime pine growth in this context [21,54,56]. Indeed, in field conditions, plant nutrient uptake is affected by biotic, e.g., mycorrhization [22] or abiotic factors, such as nutrient availability [18] or soil structure [41], which makes it difficult to study the specific effects of nutrient uptake on growth. In sake of simplicity and for enabling us to monitor the plant uptake rate of phosphorus, our experiment was therefore operated under hydroponic conditions where the nutrient addition rate is controlled accurately.…”
Section: Introductionmentioning
confidence: 99%